Do Embedded and Peripheral Corporate Social Responsibility Activities Lower Employees’ Turnover Intentions? - Liu, Yumin; Ijlal, Kamran; Hanif, Muhammad Shehzad; Khurshid, Aitzaz; Ahmed, Zeeshan (Frontiers in Psychology, 2022)
Corporate social responsibility (CSR) remains a topic of interest for both theory and practice due to its multifaceted avenues and potential for growth. We have chosen embedded CSR and peripheral CSR measures to evaluate how these activities affect the employee turnover intentions via a mediation mechanism of organizational citizenship behavior (OCB). In doing so, this study addresses important stakeholder concerns and provides meaningful managerial contributions for the employers to encourage more employee participation (through lowering turnover intention) toward sustainable corporate performance. This study incorporates four hypotheses that are tested in a structural equation modeling framework by employing Warp-PLS software. Data were collected from 297 employees working in firms that are renowned for their CSR initiatives. We found support for our key hypotheses leading to strong theoretical contributions to the stakeholder theory. We have addressed the main issues of stakeholders’ response to the CSR tradeoffs and have tried to develop a deeper understanding of managers in initiating peripheral and embedded CSR activities for their firms.